Расчет замкнутых магнитных систем методом интегрирования по источникам поля - Жильцов, А.В. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2010)
The method of integration on the sources of the field of calculation of the magnetic fields is perfected in piece-homogeneous environments. At the decision of integral equation by the method of progressive approximations on every step the law of complete current is used in an integral form for one or a few reserved contours. At replacement of integral equation by the system of linear algebraic equalizations it is complemented accordingly by one or a few equations written with the use of law of complete current in an integral form. This reception allows substantially to reduce time of account and error of determination of the field. Keywords: design of the magnetostatic fields, method of integration on the sources of the field, increase of efficiency.